2009
DOI: 10.1007/s11251-009-9096-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving early reading comprehension using embodied CAI

Abstract: An embodied approach to reading comprehension suggests that emerging readers must learn to map words and phrases onto their remembered experiences, but this is made difficult by the necessity of focusing attention on decoding. Having children manipulate toys to correspond to what they are reading overcomes this problem, but introduces its own problem for the classroom, namely having to provide a classroom full of children with manipulative. In this article, we demonstrate that having first-and second-grade chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 23 publications
3
60
0
2
Order By: Relevance
“…Accumulating evidence from embodied cognition research supports the argument that action enhances comprehension (Asher 1977;Glenberg and Goldberg 2011;Glenberg et al 2004;Tellier 2008). In recent years, the findings obtained from brain research also echo the view that language processing is an embodied process (Aziz-Zadeh and Damasio 2008; Willems and Casasanto 2011); that bodily action in the contextual environment and the person's perceptual experiences are inseparable during the cognition process.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Accumulating evidence from embodied cognition research supports the argument that action enhances comprehension (Asher 1977;Glenberg and Goldberg 2011;Glenberg et al 2004;Tellier 2008). In recent years, the findings obtained from brain research also echo the view that language processing is an embodied process (Aziz-Zadeh and Damasio 2008; Willems and Casasanto 2011); that bodily action in the contextual environment and the person's perceptual experiences are inseparable during the cognition process.…”
Section: Introductionmentioning
confidence: 72%
“…Studies in line with embodied cognition have observed different roles of actions in cognitive processes and have suggested that human mind is closely connected to sensorimotor experience. Several general theories of embodied cognition, such as those proposed by Glenberg et al (Glenberg et al 2004;Glenberg and Goldberg 2011;Glenberg and Kaschak 2002) and Barsalou (2008) argued that the cognitive process develops when a tightly coupled system emerges from interactions between organisms and their environment, with the interactions being real-time and goal-directed (Cowart 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, after a brief training, similar findings were obtained when children were instructed to imagine manipulating the toys. In addition, manipulating images of toys on a computer screen benefits children's learning to a similar extent as physical manipulation of toys (Glenberg et al 2011). Glenberg et al (2011) also showed that, compared to re-reading, manipulating toys on a computer results in better comprehension after an interval of 1 week.…”
Section: Manipulationmentioning
confidence: 91%
“…In addition, manipulating images of toys on a computer screen benefits children's learning to a similar extent as physical manipulation of toys (Glenberg et al 2011). Glenberg et al (2011) also showed that, compared to re-reading, manipulating toys on a computer results in better comprehension after an interval of 1 week. These findings encourage the use of active manipulation of objects during instruction and suggest that his is an effective way to enhance comprehension.…”
Section: Manipulationmentioning
confidence: 91%
“…Manipulating digital objects on a screen can help students focus on the learning content (Glenberg, Goldberg, & Zhu, 2009). The interactivity and manipulability of virtual manipulatives can be used by a student to draw attention to relevant properties (Moyer-Packenham & Bolyard, 2016).…”
Section: Manipulations Th Rough Input Devices and Student Attentionmentioning
confidence: 99%